Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To use the elimination method, the coefficient of one variable in one equation must be the opposite number of the coefficient of the same variable in the second equation.
[tex]4x-3y=8 \\ 5x-2y=-11[/tex]
Here you can multiply the first equation by 2, and the second equation by -3.
[tex]4x-3y=8 \ \ |\cdot 2 \\ 5x-2y=-11 \ \ |\cdot (-3) \\ \\ 8x-6y=16 \\ -15x+6y=33[/tex]
Now you just add the equations by sides and solve for one variable.
[tex]8x-6y=16 \\ \underline{-15x+6y=33 } \\ 8x-6y-15x+6y=16+33 \\ 8x-15x=16+33 \\ -7x=49 \\ x=-7[/tex]
Now you solve for the other variable by substituting -7 for x in one of the equations.
[tex]4x-3y=8 \\ 4 \cdot (-7)-3y=8 \\ -28-3y=8 \\ -3y=8+28 \\ -3y=36 \\ y=-12[/tex]
You could choose x at the beginning as well. Then you'd have:
[tex]4x-3y=8 \ \ |\cdot (-5)\\ 5x-2y=-11 \ \ |\cdot 4 \\ \\ -20x+15y=-40 \\ \underline{20x-8y=-44 \ \ \ \ \ \ } \\ -20x+15y+20x-8y=-40-44 \\ 15y-8y=-40-44 \\ 7y=-84 \\ y=-12 \\ \\ 4x-3y=8 \\ 4x-3 \cdot (-12)=8 \\ 4x+36=8 \\ 4x=8-36 \\ 4x=-28 \\ x=-7[/tex]
So the answer is:
[tex]x=-7 \\ y=-12[/tex]
[tex]4x-3y=8 \\ 5x-2y=-11[/tex]
Here you can multiply the first equation by 2, and the second equation by -3.
[tex]4x-3y=8 \ \ |\cdot 2 \\ 5x-2y=-11 \ \ |\cdot (-3) \\ \\ 8x-6y=16 \\ -15x+6y=33[/tex]
Now you just add the equations by sides and solve for one variable.
[tex]8x-6y=16 \\ \underline{-15x+6y=33 } \\ 8x-6y-15x+6y=16+33 \\ 8x-15x=16+33 \\ -7x=49 \\ x=-7[/tex]
Now you solve for the other variable by substituting -7 for x in one of the equations.
[tex]4x-3y=8 \\ 4 \cdot (-7)-3y=8 \\ -28-3y=8 \\ -3y=8+28 \\ -3y=36 \\ y=-12[/tex]
You could choose x at the beginning as well. Then you'd have:
[tex]4x-3y=8 \ \ |\cdot (-5)\\ 5x-2y=-11 \ \ |\cdot 4 \\ \\ -20x+15y=-40 \\ \underline{20x-8y=-44 \ \ \ \ \ \ } \\ -20x+15y+20x-8y=-40-44 \\ 15y-8y=-40-44 \\ 7y=-84 \\ y=-12 \\ \\ 4x-3y=8 \\ 4x-3 \cdot (-12)=8 \\ 4x+36=8 \\ 4x=8-36 \\ 4x=-28 \\ x=-7[/tex]
So the answer is:
[tex]x=-7 \\ y=-12[/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.